The Science of Religion and the Sociology of Knowledge - Smart, Ninian (Princeton : Princeton University Press, 2015)
Ambitiously undertaking to develop a strategy for making the study of religion ""scientific,"" Ninian Smart tackles a set of interrelated issues that bear importantly on the status of religion as an academic discipline. He draws a clear distinction between studying religion and ""doing theology,"" and considers how phenomenological method may be used in investigating objects of religious attitudes without presupposing the existence of God or gods. He goes on to criticize projectionist theories of religion (notably Berger's) and theories of rationality in both religion and anthropology. On th.
Description based upon print version of record.
Contents
Keywords: Religion; PHILOSOPHY / Religious; Religion; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books